The Perception of Physical Activity and Sports Professionals’ Competence in Working With Individuals With Disabilities in Spain - Gutiérrez-Conejo, María; González-Rivera, María-Dolores; Campos-Izquierdo, Antonio (Frontiers in Psychology, 2021)
The importance of professional competence lies in the effective application of job-oriented knowledge and skills which guarantee one’s successful adaptation to the work. This study analyzes the perception of the importance of physical activity and sports (PAS) professionals’ competence in working with individuals with disabilities in Spain. As a descriptive quantitative study, face-to-face interviews were conducted through a survey to extract the data. The sample consisted of 214 PAS professionals working with people with disabilities. According to the results, the analyzed constituents of professional competence are important for adequate performance (>65%), with the exception of competences of leadership and use of new technologies (<50%). It was also found that the perceived importance of each element of professional competence varies according to age, experience and training. Based on the obtained results, the degree of importance of each constituent of professional competence and its implication for the access of people with disabilities to high-quality physical activity and sports services was determined.